Efektivitas Sistem Bioflog dalam Mendukung Pertanian Berkelanjutan: Studi Kasus di Pondok Pesantren Al Kautsar 561 - Aini Dewi Maryan; Adenty Oktavianty; Rina Nuryati; Candra Nuraini (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Research aims to look at the implementation of the bioflog system at the Al Kautsar 561 Islamic Boarding School as an effort to support sustainable agriculture. Using a qualitative approach with descriptive design, this research analyzes the implementation process, benefits and obstacles faced. The research results show that the bioflog system has succeeded in increasing the productivity of tilapia cultivation significantly. Apart from that, this system is also able to reduce the use of chemical fertilizers and improve water quality. Factors that support success include full support from Islamic boarding school administrators and active involvement of students. However, this research also identified several obstacles such as limited resources and weather fluctuations. This research concludes that the bioflog system has great potential to become a model of sustainable agriculture in Islamic boarding school environments. It is hoped that the results of this research can become a reference for other Islamic boarding schools in implementing similar systems and encourage the development of policies that support sustainable agriculture.